2021
DOI: 10.4171/rmi/1277
|View full text |Cite
|
Sign up to set email alerts
|

The talented monoid of a directed graph with applications to graph algebras

Abstract: It is a conjecture that for the class of Leavitt path algebras associated to finite directed graphs, their graded Grothendieck groups K gr 0 are a complete invariant. For a Leavitt path algebra L k .E/, with coefficients in a field k, the monoid of the positive cone of K gr 0 .L k .E// can be described completely in terms of the graph E. In this note we further investigate the structure of this "talented monoid", showing how it captures intrinsic properties of the graph and hence the structure of its associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The talented monoid of a row-finite directed graph E = (E 0 , E 1 , r, s), denoted by T E , is the commutative monoid generated by {v(i) : v ∈ E 0 , i ∈ Z} such that v(i) = e∈s −1 (v) r(e)(i + 1) for every i ∈ Z and every v ∈ E 0 that is not a sink. The additive group Z of integers acts on T E by monoid automorphisms by shifting indices: for each n, i ∈ Z and v ∈ E 0 , define n v(i) = v(i + n), which extends to an action of Z on T E [3]. Monoids with a group Γ acting (by monoid automorphisms) on it, called Γ-monoids, was first introduced in the paper of Hazrat and Li [1] as a tool in the study of talented monoids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The talented monoid of a row-finite directed graph E = (E 0 , E 1 , r, s), denoted by T E , is the commutative monoid generated by {v(i) : v ∈ E 0 , i ∈ Z} such that v(i) = e∈s −1 (v) r(e)(i + 1) for every i ∈ Z and every v ∈ E 0 that is not a sink. The additive group Z of integers acts on T E by monoid automorphisms by shifting indices: for each n, i ∈ Z and v ∈ E 0 , define n v(i) = v(i + n), which extends to an action of Z on T E [3]. Monoids with a group Γ acting (by monoid automorphisms) on it, called Γ-monoids, was first introduced in the paper of Hazrat and Li [1] as a tool in the study of talented monoids.…”
Section: Introductionmentioning
confidence: 99%
“…Definition 8. [3] Let M be a monoid and Γ a group. M is said to be a Γ-monoid if there is an action ϕ : Γ × M → M of Γ on M via monoid automorphism, that is, ϕ is an action which satisfies: for all α ∈ Γ and x, y ∈ M , ϕ((α, x * y)) = ϕ((α, x)) * ϕ((α, y)).…”
Section: Introductionmentioning
confidence: 99%
“…Proposition 2.3. [9] Let Γ be a group and T a Γ-monoid. For x ∈ T , the Γ-order-ideal generated by x, denoted by x , is given by the set…”
Section: Introductionmentioning
confidence: 99%
“…In this form the talented monoids were introduced in [8] and further studied in [6,9]. It was shown that the talented monoid captures certain geometry of its associated graph, and hence the algebraic properties of the corresponding Leavitt path algebra.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a graph has Condition (L), i.e., any cycle has an exit, if and only if the group Z acts freely on T E [8]. Or, the period of a graph, i.e., the greatest common divisor of the lengths of all closed paths based a vertex, can be described completely via its associated talented monoid [6]. Using these results one can give finer descriptions of purely infinite simple Leavitt path algebras associated to graphs.…”
Section: Introductionmentioning
confidence: 99%